HISTORY, STRUCTURE AND PERFORMANCE TECHNIQUES OF THE PIANO - Qilicheva Gavhar Farhodovna; Umurzoqova Laylo Baxtiyor qizi (Modern American Journals, 2025)
This article discusses how learning to play the piano and developing performance skills involves not only performing technical exercises, but also developing musical expression, thinking, and imagination, and systematically implementing the recommendations below will help you achieve good results over time.
Keywords: Piano, performance, skill, technique, mastery, style.